Trend inflation and structural shocks - Bowen Fu; Ivan Mendieta-Munoz (ZBW - Leibniz Information Centre for Economics, 2025)
This paper studies the effects of key underlying macroeconomic variables on the trend inflation rate in the USA. To do so, we consider eight structural shocks that incorporate a broad set of information for the US economy and that can be regarded as the main structural determinants of the latter. Using a Bayesian estimation procedure, we estimate the effects of these structural shocks on the trend inflation rate via an unobserved components model with stochastic volatility and structural shocks. We document the following results. First, four structural shocks have significant and quantitatively important effects on the trend inflation rate. Price mark-up and government policy shocks increase trend inflation, which suggests that these shocks tend to have long-run inflationary effects. Finance and productivity shocks decrease trend inflation, thus suggesting that these shocks tend to have long-run deflationary effects. Second, during the Global Financial Crisis of 2007-9, the trend in inflation became more volatile because of the combined effects derived from these four structural shocks.
Keywords: C11; C32; E30; E31; 330; trend inflation; structural shocks; state space models; unobserved components